2023
DOI: 10.3390/ijerph20021283
|View full text |Cite
|
Sign up to set email alerts
|

Association between Social Participation and Remaining Teeth and Urban–Rural Difference among Older Adults in China

Abstract: Oral health is an important part of older adults’ general health. The study examined the association between social participation (formal and informal) and remaining teeth and the urban–rural difference based on a national survey of older adults in China. The data of older adults were extracted from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) and analyzed. A total of 11,948 respondents were ultimately involved, including 6836 urban respondents and 5112 rural respondents. Informal social participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Specifically, those with significant tooth loss were observed to have a reduced social participation level, which in turn was associated with increased functional limitations. Another study utilizing data from CLHLS similarly indicated that social participation had a significant relationship with the number of remaining teeth [39]. However, in this study's hypothesis, social participation was considered the cause, and tooth loss was viewed as the outcome.…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, those with significant tooth loss were observed to have a reduced social participation level, which in turn was associated with increased functional limitations. Another study utilizing data from CLHLS similarly indicated that social participation had a significant relationship with the number of remaining teeth [39]. However, in this study's hypothesis, social participation was considered the cause, and tooth loss was viewed as the outcome.…”
Section: Discussionmentioning
confidence: 74%
“…19 A study in China showed that social participation was positively associated with the self-reported number of teeth, after adjustment for sociodemographic factors, health behaviors, sleep duration, physical functioning, comorbidities, and cognitive function. 20 Longitudinal studies from other countries with aging populations would be valuable to confirm these preliminary findings. Brazil has one of the largest aging populations in the world, with a quarter of its population aged 50 or more years (equivalent to 54 million people) and 30 million Brazilians aged 60 or more years.…”
Section: Introductionmentioning
confidence: 90%
“…The magnitude of impairment was largest in vision, followed by tooth and hearing loss 19 . A study in China showed that social participation was positively associated with the self‐reported number of teeth, after adjustment for sociodemographic factors, health behaviors, sleep duration, physical functioning, comorbidities, and cognitive function 20 . Longitudinal studies from other countries with aging populations would be valuable to confirm these preliminary findings.…”
Section: Introductionmentioning
confidence: 94%